Academic Impairment, Social Support and Resilient Behavior Among Physically-Challenged in-School Adolescents - Esohe G. Ehondor; Olajide M. Daramola; Emmanuel Etim Uye (Fenomena, 2025)
Various stakeholders, including the government, have often neglected the educational needs of physically challenged in-school adolescents in Nigeria. Empirical studies examining the relationship between academic impairment, social support, and resilient behavior in this population remain scarce, particularly within the Nigerian context. Therefore, this study investigated academic impairment and social support as predictors of resilient behavior among physically challenged in-school adolescents in Lagos and Ekiti States in South-West Nigeria. A cross-sectional research design was employed, and purposive sampling was used to select the two states. Data were collected from 374 physically challenged in-school adolescents using validated measurement scales. The data were analyzed using multiple regression and independent samples t-tests to test four hypotheses at a significance level of p < 0.01. The results showed that both academic impairment and support from significant others independently predicted resilient behavior. Furthermore, academic impairment and social support jointly predicted resilience. The findings highlight the crucial role of significant others as a source of social support. The study underscores the need for the government and stakeholders to enhance infrastructure in special schools to improve learning experiences. This research is novel as it is the first to examine these variables across two Nigerian states.